ECONOMIC REVITALIZATION PROGRAM in ACHIEVING THE HAZE-FREE ASEAN TARGET 2020 by THE RIAU PROVINCE’S PEATLAND RESTORATION AGENCY - nizmi, yusnarida eka; Olivia, Yessi; Retnaningsih, Umi Oktyari; Saeri, M.; Jama’an, Ahmad; Alfajri, Alfajri (Berumpun: International Journal of Social, Politics, and Humanities, 2021)
This study analyses the implementation of good governance principles for the economic revitalization program under Riau Province’s Badan Restorasi Gambut (Peatland Restoration Agency) supervision. One of the aims of this program is to support the haze-free ASEAN 2020 roadmap. Riau province is an area prone to forest fire disasters. Its peatland area, which is twice as large as Malaysia’s peatland, have a very high potential for damage due to forest fires. To mitigate the damages, BRG initiated the 3R program: Rewetting, Revegetation, and Revitalization. What makes this topic interesting is BRG emphasizes the aspects of economic empowerment of local communities to prevent further forest and peatland damages. To assess the implementation of BRG’s program, our research team conducted several interviews with representatives from Indonesia’s Ministry of Environment and Forestry, NGOs, academics, farmers, and villages’ facilitators who assisted local communities that received the BRG’s assistance packages. Our study shows that BRG’s economic revitalization program had succeeded in creating small scale economic activities such as honey industry, pineapple farming, and catfish farming. However, the ineffective coordination and communication between BRG and the local communities had prevented them from constructing an effective method to prevent future forest fires.